Penerapan Converter Osiloskop MDS 9200 pada Tegangan DC untuk Pengujian Penyearah Satu Phase pada Praktikum Elektronika Daya - I Wayan Lastera (UIN Sunan Kalijaga Yogyakarta, 2023)
Oscilloscopes are widely used in electrical engineering laboratories for the smooth implementation of practicum. In power electronics practicum, this tool is used to display electric waveforms. To display the electric waveform at a certain magnitude properly, it is necessary to be equipped with an oscilloscope converter. To find out the test voltage range of the MDS 9200 Oscilloscope at DC voltage with the application of a converter, this research was carried out. The research was carried out for a two-stage full-wave single-phase rectifier, first testing the MDS 9200 Oscilloscope at a DC voltage without a converter, the second with a converter. The test results were collected, analyzed descriptively, the test voltage range of the MDS 9200 Oscilloscope at a DC voltage without a converter was between 0 to 11.71 volts, with a converter the test voltage range was from 0 to 220 volts. The application of the converter is able to widen the test voltage range of the MDS 9200 Oscilloscope at DC voltage so that it can be used as a reference for similar tests.